Analysis Of Go-Jek Effect On Community Mobility ( A Study Case: www.go-jek.com) - Koko Subchan Faizar Nur; Daisy Mui Hung Kee; Muh Parhan; Ragastara Atrasyan Ramadhany; Tony Yanuar Syahputra (AIBPM Publisher, 2019)
The basic of this project is to develop analysis of GO-JEK effect on community mobility in Indonesia. The mediums that we will use are Interviews with the people in community. In terms of transportation, there are still many things that make people feel uncomfortable. This was well utilized by Nadiem Makarim, to establish a motorbike taxi service provider (online). GO-JEK is considered to have a major influence on the community economy and public transportation. We try to analyze whether GO-JEK is the most desirable alternative for society when compared to other motorbike taxi applications, how it affects the community, and what analysis needs to be developed by GO-JEK's shortcomings.